COMPARISON OF TRIGGER POINT THERAPY AND CONVENTIONAL PHYSICAL THERAPY IN TENSION TYPE HEADACHES - Saima Aslam; Aqeel Ahmed; Sundas Zia; Noureen Farooq (The Rehabilitation Journal, 2019)
Objective: To compare the effectiveness of trigger point release and conventional physical therapy in tension type headaches. Materials & Methods: Randomized controlled trial (RCT) conducted from 18th February 2017 to 13 July 2018, at Isra institute of Rehabilitation Sciences (IIRS) Isra University, Islamabad Campus, Pakistan. A total of n=31 healthy individuals with tension type headache below the age of 50 years, were selected through non probability convenient sampling technique and randomly divided into conventional physical therapy and trigger point therapy group. The pain and Headache disability index data was compared at baseline and during and after the intervention while quality of life was measured pre and post the sessions. For within the groups changes RM-ANOVA was used and for between the groups differences independent sample t-test was used. Results: The results showed that pain was significantly reduced at the end of intervention in conventional physical therapy group as compare to trigger point therapy group (1.31±0.47 ver. 2.13±0.64, p<0.001). Regarding headache disability index, at the end of intervention trigger point therapy group show better results as compare to conventional physical therapy group (32.75±12.83 ver. 53.27±26.57, p=0.01). While comparing quality of life between the groups, no significant difference was observed after intervention. Conclusion: It was concluded that both conventional physical therapy and trigger point therapy are effective in the management of tension type headache. It decreased pain and disability caused by headache but no effect on quality of life due to shorter duration of study.